Fungal diversity for enhanced sugar production comparing rotting and non-rotting fungi in pretreatment of empty palm oil bunches - INA MONICA FIRSTY; RATNA SETYANINGSIH; SRI SUGIWATI; ATANU KUMAR DAS; RONI MARYANA (Society for Indonesian Biodiversity, 2025)
Abstract. Firsty IM, Setyaningsih R, Sugiwati S, Das AK, Maryana R. 2025. Fungal diversity for enhanced sugar production comparing rotting and non-rotting fungi in pretreatment of empty palm oil bunches. Biodiversitas 26: 2117-2129. Empty Palm Oil Bunch (EPOB) is an abundant lignocellulosic biomass in Indonesia with significant potential for conversion into valuable products. This study explores various types of fungi in enhancing sugar production from EPOB. This study compared white-rot fungi (Trametes versicolor and Pycnoporus cinnabarinus) with non-white-rot fungi (Aspergillus niger, Aspergillus terreus, Trichoderma harzianum, and Trichoderma viride) to see the effect on lignin and cellulose content, as well as enzyme activities. Using Response Surface Methodology (RSM), this study optimized temperature, pH, and substrate concentration. Among the fungi, A. niger showed the best results for lignin removal (7.58 ± 1.5%) and cellulose increase (33.56 ± 0.00%). P. cinnabarinus had the highest laccase and MnP activities (9.26 and 123.81 U/mL), while A. niger produced the highest LiP activity (3276.8 U/mL). X-Ray Diffraction (XRD) analysis revealed a reduction in crystallinity in the pretreated samples. The best pretreatment conditions with A. niger were found to be 30°C, pH 5, and 7 g of EPOB, achieving the highest lignin removal (14.21 ± 0.50%). A. niger also led to the highest cellulose content (53.08%) at 25°C. Enzyme hydrolysis of A. niger-pretreated EPOB produced 1.09 g (36.30%) of reducing sugar after 48 h at 50°C. This study highlights how leveraging fungal diversity can optimize biomass pretreatment processes.